Evolving IoT: Based Smart Healthcare Monitoring System - Pothumahanty Sai Jyothi; Naresh Patnana (International Journal of Robotics and Automation in Mechanics, 2023)
The continuous progress in technology has led to remarkable enhancements in various aspects of human life, including healthcare. Within the healthcare sector, practitioners and experts are embracing new technologies to significantly improve the implementation of medical services. The Internet of Things (IoT) has emerged as a crucial foundation for various innovative healthcare technologies, such as heartbeat sensors, ECGs, and blood pressure sensors, each equipped with microcontrollers to read and interpret data from the sensors as needed. While these advancements have brought many benefits, the cost of healthcare services has also increased, making them less accessible to some individuals. Additionally, understanding the working of advanced healthcare system can be challenging for many people, leading to increased reliance on medical practitioners for interpretation. To address these challenges, in this paper a remote healthcare monitoring system is developed and designed to deduce patients' vital signs using sensors and provide easily accessible data to the public. Main objective of this work was to create a simplified mechanism that enables patients' families to continuously monitor their health status. The healthcare monitoring system operates by collecting data through sensors and transmitting it to the cloud. the gathered information undergoes processing and analysis to enable remote viewing. The analyzed information is shared with guardians, doctors, and family members, facilitating easy access to vital health data and promoting better healthcare management. For this process a prototype model is developed and validated the results.
Keywords: BMI; Heartbeat; Internet of Things; Medicine reminder; Smart Healthcare; Social Distancing alert